Spotless arc activated high-rate deposition using novel dual crucible technology for titanium dioxide coatings - Scheffel, Bert; Metzner, Christoph; Modes, Thomas (International Conference on Plasma Surface Engineering, 2013)
For deposition of thin oxide coatings there are a lot of qualified PVD processes today. If high productivity or large-area coating is necessary for economic reasons processes with high deposition rate are reasonable. Using electron beam (EB) evaporation all inorganic materials can be evaporated with high rates. Microstructure of coatings deposited by EB-evaporation depends on substrate temperature during layer growth and melting temperature of coating material. Particularly in case of high melting materials columnar and porous microstructure is obtained. For large area coating several plasma sources have been developed in order to enhance energy of condensing particles and to get denser layer microstructure. Spotless arc Activated Deposition (SAD) combines electron beam high-rate evaporation using axial gun and a spotless arc discharge burning in metal vapor on hot evaporating cathode [2]. The SAD process is suitable for evaporation of high-melting metals like titanium, zirconium or tantalum providing high deposition rate up to 2000 nm/s. Moreover plasma-activation enables reactive mode of operation and deposition of oxides, nitrides or other compounds with a high rate in the range of 20 to 100 nm/s. A Spotless arc is an arc discharge burning in metal vapor which is obtained if the cathode temperature is high enough to enable high thermionic electron emission current density. Spotless mode results in relatively low cathodic arc current density and droplets known from arc evaporators with cold cathode are completely avoided [3]. Nevertheless high DC arc current up to 2000 A is possible. Recent work has shown that SAD process is well suited for deposition of titanium dioxide coatings based on evaporation of titanium and reactive processing in oxygen atmosphere [4]. TiO2 layers were deposited at very high deposition rates between 40 and 70 nm/s. Depending on process conditions amorphous coatings or crystalline phases were obtained. Coatings consisting of anatase phase show very good properties concerning photoinduced superhydrophilicity and photocatalysis. Transparent layers with high refractive indexes in the range of 2.30 and 2.58 could be reached.